FRI0094 Prevalence of Vitamin D Deficiency in Rheumatoid Arthritis (RA): Data from the Comedra Cohort. (10th June 2014) - Cecchetti, S.; Soubrier, M.; Galan, P.; Pereira, B.; Mouterde, G.; Dougados, M.
Abstract : Background: Serum levels of vitamin D (VitD) are usually inversely correlated with RA activity. However, the prevalence of VitD deficiency does not appear to differ from that of the general population. Hypertension (HT) and low levels of HDL-cholesterol (HDL-c) –two cardiovascular (CV) risk factors with an increased prevalence in RA – are inversely correlated with VitD levels. Objectives: Determine the prevalence of VitD deficiency in RA patients versus a control population. Detect correlations between VitD levels and RA disease activity and/or characteristics, and between VitD levels and CV risk factors. Methods: The COMEDRA study evaluated the impact of a visit with a nurse on the management of comorbidities in RA patients. VitD and lipids assays were performed in all patients. Controls were from the SUVIMAX cohort and were matched for gender, age, latitude and season during which samples were taken for assay. VitD deficiency was defined as VitD<10 ng/ml and VitD insufficiency as VitD between 10 and 29.9 ng/ml (VDI). Results: 894 patients (79.3% women) with an average disease duration of 11.2 years [6.3 – 19.1] were analyzed. RA was erosive in 73.3% of patients and 83.9% had positive RF or anti-CCP antibodies. The DAS28ESR was 3.0±1.3. 630 patients (70.4%) were treated with biologic therapy and 341 (38.1%) received glucocorticoids (5.5±5.7 mg/day). BMI was 25.1±4.8. SBP was 124.9±16.5 mmHg, and DBP 75.6±11.4 mmHg. Total cholesterol was 2.2±0.5 g/l, LDL-c was 1.3±0.4 g/l, HDL-c was 0.7±0.2 g/l. 147 patients (16.4%) were smokers and 52 (5.8%) were diabetic. VitD levels were in the normal range in 362 patients (40.5%), whereas 501 patients (56.0%) had VitD insufficiency and 31 (3.5%) had VitD deficiency. Comparison of 861 RA patients with 861 matched controls revealed that the RA patients had a lower prevalence of VitD insufficiency (RA: 480 (55.8%) vs. controls: 508 (59%); p=0.04) and of VitD deficiency (RA: 31 (3.6%) vs. controls: 45 (5.23%); p=0.04). Among RA patients, males had a higher frequency of VitD insufficiency (117 (63.3%) vs 384 (54.2%); p=0.04) and VitD deficiency (8 (4.3%) vs.23 (3.2%); p=0.04 in males vs females respectively). There was no difference according to latitude, but the prevalence of VitD insufficiency and VitD deficiency were higher in springtime. Univariate analysis found an inverse correlation between VitD levels and RA activity defined by DAS28CRP (p=0.02), SDAI (p=0.05) and CDAI (p=0.05), but only a trend for DAS28ESR (p=0.08). No correlation was found with antibody status or with treatments. VitD levels were inversely correlated with BMI (p<0.001) but not with blood pressure, total-c, LDL-c, HDL-c or diabetes. Conclusions: This study confirms that VitD is inversely correlated with RA activity and BMI but not with other CV risk factors. The prevalence of VitD deficiency was lower than in the control population, which could be explained by the fact that RA patients more frequently received VitD supplementation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5014